Bangladesh Economic Update, May 2012 - World Bank (Washington, DC, 2017)
Gross Domestic Product (GDP) growth has moderated from 6.7 percent in FY11 to 6.3 percent in FY12 due to unfavorable external economics and internal supply constraints. Monetary policy remained accommodative for most of 2011 but gradual tightening is occurring. With the high fiscal deficit and domestic borrowing by Government, monetary policy is now bearing the brunt of macroeconomic policy adjustment. The balance of payments (BoP) is on a deteriorating track, with reserves falling to below three months of imports and export growth turning negative in March 2012. A coordinated policy response is required to ease macroeconomic pressures and improve growth prospects. Key actions include the need to create fiscal space, contain government borrowing to mitigate the risk of crowding out of credit to the private sector, better regulate the capital market, and stimulate investment and job growth in the export sector. Unlike in 2008, Bangladesh has insufficient policy space to avert the negative impact of a global slowdown through fiscal stimulus packages and monetary easing.